Treatment outcomes of patients co-infected with tuberculosis and HIV at Chiang Mai university hospital, Thailand - S. Limmahakhun (2018)
Summary: Thailand has been greatly affected by the tuberculosis (TB) and HIV syndemic. This study aimed to determine treatment outcomes among HIV/TB co-infected patients. A retrospective cohort study was conducted at Chiang Mai University Hospital from 1 January 2000 to 31 December 2009. Of 171 patients, 100 patients were male (58.5%) and the mean age was 36.8 ± 8.0 years. Seventy-two patients (42.1%) had pulmonary tuberculosis. Median CD4+ count before TB treatment was 69 cells/mm3(interquartile range [IQR] 33, 151). The overall mortality was 3.5% (6 patients). Immune reconstitution inflammatory syndrome (IRIS) occurred in eight patients (6.0%). Disseminated TB infections increased risk of death (odds ratio [OR] = 2.55, 95% confidence interval [CI] 1.25, 5.18) and IRIS (OR = 9.16, 95% CI 1.67, 50.07). Initiating combination antiretroviral therapy (cART) within two months after TB treatment increased risk of IRIS (OR = 6.57, 95% CI 1.61 -26.86) and physicians caring for HIV/TB co-infected patients should be aware of this condition.